The future of environmental ethics - Rolston, Holmes, 1932-2025, speaker; Landers, Heather, speaker; Colorado State University, producer (Colorado State University. Libraries, 2010)
Lecture covers consideration of the following topics: 1. A managed earth and the end of nature? 2. Global warming: too hot to handle? 3. Human nature: Pleistocene appetites? 4. Sustainable development vs. sustainable biosphere; 5. Biodiversity: good for us/good in itself; 6. Earth ethics.
Lecture presented at TILT, The Institute for Learning and Teaching at Colorado State University on September 22, 2010.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: environmental ethics; technosphere; ecological ethics; global warming; wildlife reserves; conservation; ruptures of history; recycling; sustainable development; humans; nature; environmentalism; biosphere; millennium ecosystem assessment